Plant Growth Promoting Abilities of Novel Burkholderia-Related Genera and Their Interactions With Some Economically Important Tree Species - Munusamy Madhaiyan; Govindan Selvakumar; Tan HianHwee Alex; Lin Cai; Lianghui Ji; Lianghui Ji (Frontiers in Sustainable Food Systems, 2021)
A survey of bacterial endophytes associated with the leaves of oil palm and acacias resulted in the isolation of 19 bacterial strains belonging to the genera Paraburkholderia, Caballeronia, and Chitinasiproducens, which are now regarded as distinctively different from the parent genus Burkholderia. Most strains possessed one or more plant growth promotion (PGP) traits although nitrogenase activity was present in only a subset of the isolates. The diazotrophic Paraburkholderia tropica strain S39-2 with multiple PGP traits and the non-diazotrophic Chitinasiproducens palmae strain JS23T with a significant level of 1-aminocyclopropane-1-carboxylate (ACC) deaminase activity were selected to investigate the influence of bacterial inoculation on some economically important tree species. Microscopic examination revealed that P. tropica S39-2 was rhizospheric as well as endophytic while C. palmae JS23T was endophytic. P. tropica strain S39-2 significantly promoted the growth of oil palm, eucalyptus, and Jatropha curcas. Interestingly, the non-diazotrophic, non-auxin producing C. palmae JS23T strain also significantly promoted the growth of oil palm and eucalyptus although it showed negligible effect on J. curcas. Our results suggest that strains belonging to the novel Burkholderia-related genera widely promote plant growth via both N-independent and N-dependent mechanisms. Our results also suggest that the induction of defense response may prevent the colonization of an endophyte in plants.